A millimeter-scale observation of the competitive effect of phosphate on promotion of arsenic mobilization in sediments. (August 2017) - Sun, Qin; Ding, Shiming; Zhang, Liping; Chen, Musong; Zhang, Chaosheng
Abstract: A millimeter-scale investigation is key to the understanding of the competitive effects of phosphate(P) on arsenic(As) mobility in sediments by taking the great biogeochemical heterogeneity of the sediments into consideration. In this study, a microcosm experiment was performed in this aspect using high-resolution dialysis and diffusive gradients in thin films (DGT) to simultaneously measure dissolved and labile P, As, and iron (Fe) in sediments, respectively. With the increase of P content in water from 0.02 mg L −1 to 0.20 and 2.4 mg L −1, consistent release of As from sediments was observed. The concentrations of DGT-labile As increased significantly especially in the upper sediment layer (up to 12 times of the 0.02 mg P L −1 treatment) due to the competition of phosphate, which corresponded well to the increase in DGT-labile P. There was limited increase in dissolved P and As contents due to the buffering provided by sediment solids, while the concentrations of both dissolved and DGT-labile Fe in sediments decreased. A stoichiometric calculation showed that 47% and 8% of the added P were removed through Fe(II) precipitation for the 0.20 and 2.4 mg P L −1 treatments, respectively, which greatly suppressed the release of As induced by P competition for the 0.20 mg P L −1 treatment. The DGT-induced fluxes in sediments (DIFS) modeling showed an increase in solid resupply to pore water As from elevation of water P through the increases of the desorption rate constant from 5.4 to 31( × 10 −7 ) s −1 and the sorption rate constant from 1.8 to 22( × 10 −4 ) s −1 . Graphical abstract: Highlights: The competitive effect of P on As release in sediments was first investigated on a mm scale. Elevation of water P increased DGT-labile P and As but it decreased DGT-labile Fe. Limited increases in dissolved P and As appeared due to sediment buffering. Resupply ability of sediment solids for pore water As increased with elevation of water P. Fe(II) precipitation greatly suppressed P competition on As mobilization under low P treatment. Abstract : Competition effect of P on promotion of As mobilization in sediments was observed on a mm scale.